Effects of deviating the Th2-response in murine mercury-induced autoimmunity towards a Th1-response - HÄGGQVIST, B (Blackwell Science Inc, 2003)
T-helper cells type 1 (Th1) and type 2 (Th2) play an important role in the pathogenesis of autoimmune diseases. In many Th1-dependent autoimmune models, treatment with recombinant interleukin-12 (rIL-12) accelerates the autoimmune response. Mercury-induced autoimmunity (HgIA) in mice is an H-2 regulated condition with antinucleolar antibodies targeting fibrillarin (ANoA), systemic immune-complex (IC) deposits and transient polyclonal B-cell activation (PBA). HgIA has many characteristics of a Th2 type of reaction, including a strong increase of IgE, but disease induction is critically dependent on the Th1 cytokine IFN-γ. The aim of this study was to investigate if a strong deviation of the immune response in HgIA towards Th1 would aggravate HgIA. Injections of both rIL-12 and anti-IL-4 monoclonal antibody (α-IL-4) reduced the HgCl(2)-(Hg-)induced concentration of the Th2-dependent serum IgE and IgG1, but increased the Th1-dependent serum IgG2a. The IgG-ANoA developed earlier and attained a higher titre after combined treatment, and the ANoA titre of the IgG1 isotype decreased while the ANoA titre of the Th1-associated IgG2a, IgG2b and IgG3-ANoA isotypes increased. Treatment with rIL-12 alone increased the Hg-induced IgG2a and IgG3 ANoA titres, the PBA, and the IC deposits in renal and splenic vessel walls, while treatment with α-IL-4 + Hg inhibited renal but not splenic vessel wall IC deposits. We conclude that manipulating the cytokine status, by altering the Th1/Th2 balance, will influence autoimmune disease manifestations. This might be an important way of modulating human autoimmune diseases.